Quantifying effects of the built environment on solar irradiance availability at building rooftops. Issue 2 (3rd March 2020) - Bianchi, Carlo; Overby, Matthew; Willemsen, Peter; Smith, Amanda D.; Stoll, Rob; Pardyjak, Eric R.
Abstract: Solar radiation significantly impacts the performance of buildings and integrated renewable energy technologies. Surrounding buildings may reduce the amount of radiation reaching urban building rooftops, but may also enhance solar energy availability through scattering and reflections. These effects are difficult to quantify due to the complexity of urban geometries. Here, a new parameterization that quantifies the role of urban form on the availability of rooftop solar radiation, including the effects of mutual reflections and shading, is developed and tested. We find that available rooftop solar energy may be parameterized by a simple model using only plan area fraction, average building height, and building height standard deviation. The new model is developed using the building-resolving, ray-tracing based radiation transfer model QESRadiant to simulate incident solar irradiation in 125 city models over 11 latitudes for 13 days (18, 000 simulations). The parameterization error is less than 5% for latitudes that encompass 95% of the world's population.